C‐reactive protein in adult Samoans: Population variation and physiological correlates. Issue 3 (14th July 2021) - Rivara, Anna C.; Corley, Margaret; Choy, Courtney C.; Duckham, Rachel L.; Pomer, Alysa; Reupena, Muagututia Sefuiva; Viali, Satupaitea; Naseri, Take; Kershaw, Erin E.; Crouter, Scott E.; McGarvey, Stephen T.; Bribiescas, Richard G.; et al.
Abstract: Objectives: C‐reactive protein (CRP) has been associated with adiposity and cardiometabolic disease risk in many populations but remains remarkably understudied in Pacific Islander populations. Here, we provide the first examination of correlates of CRP in adult Samoans ( n = 108, ages 35–55 years) to test the hypotheses that CRP exhibits sex‐dependent associations with measures of BMI, adiposity, and cardiometabolic disease risks. Methods: We analyzed associations between measures of adiposity (total fat mass, visceral fat mass, percent total body fat), body mass index (BMI), cardiometabolic risks, behaviors, demographics, and CRP. Unadjusted analyses of CRP were undertaken using Pearson's pairwise, and Spearman's rank correlations; one‐way analysis of variance and Kruskal–Wallis tests assessed variables by CRP quartiles. Adjusted analyses of CRP correlates were examined using generalized linear regression. Results: Serum CRP ranged from 0.08 to 13.3 mg/L (median 1.4 mg/L) and varied significantly by sex t (108) = −2.47, p = .015. CRP was weakly to moderately associated with measures of adiposity and BMI ( r and ρ ranged between 0.25 and 0.50, p < .05) and some cardiometabolic markers (including HbA1c, fasting insulin, and insulin resistance). CRP was significantly associated with percent body fat in women and men, adjusting for other variables. Conclusions: These data are among the first to demonstrate CRP correlates in a sample of adult Samoans. CRP differed by sex and was associated with BMI, adiposity, and some cardiometabolic risk markers. These data align with findings in other populations.